2016
DOI: 10.1016/j.ridd.2016.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Statistical modelling studies examining the dimensional structure of psychopathology experienced by adults with intellectual disabilities: Systematic review

Abstract: Diagnosing mental ill-health using categorical classification systems has limited validity for clinical practice and research. Dimensions of psychopathology have greater validity than categorical diagnoses but dimensional models have not had a significant impact on our understanding of mental ill-health experienced by adults with intellectual disabilities. This paper systematically reviews the methods and findings from intellectual disabilities studies that use statistical methods to identify dimensions of psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…We believe our study is the first to develop and validate a dimensional model of psychopathology experienced by adults with intellectual disabilities using robust statistical methods (Melville et al, 2016). This is also the first study to compare the predictive validity of dimensional and categorical models of psychopathology in this population.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We believe our study is the first to develop and validate a dimensional model of psychopathology experienced by adults with intellectual disabilities using robust statistical methods (Melville et al, 2016). This is also the first study to compare the predictive validity of dimensional and categorical models of psychopathology in this population.…”
Section: Discussionmentioning
confidence: 87%
“…The three statistical models included categorical diagnosis (statistical model 1); dimensional scores (statistical model 2); a full model categorical diagnosis and factor/dimensional scores (statistical model 3). All three models included socio-clinical variables found to be associated with severity and outcome in a feasibility study (age, gender, level of intellectual disabilities, living circumstances, visual impairment, hearing impairment and incontinence; Melville, 2010). Since statistical models 1 and 2 were nested within statistical model 3, they were compared to the full model using the -2 log likelihood score and likelihood ratio test.…”
Section: Predictive Validity Of Dimensional and Categorical Models Ofmentioning
confidence: 99%
“…Sturmey et al [41] additionally concluded that CBs could not be viewed as depressive equivalents in their similar correlational study as there were no particular CBs reliably associated with depression. Melville et al [42] surmised that CB was not indicative of depression because the measurement items related to depression and CB were located in different factors of an analysis of the Psychiatric Present State-Learning Disabilities Examination Scale. Other researchers also found that CB was not associated with MH problems [43,44].…”
Section: Challenging Behaviour and Mental Health Problemsmentioning
confidence: 99%
“…Due to a range of limitations, none of the existing research studies allowing an examination of the association between CB and MH can be considered definitive. The main limitations include fundamental differences in diagnostic constructs in the field of ID [42,53], inconsistent definitions of CB (as mentioned earlier, and [54]). overlap between these two problems [55•], and the practical challenges of categorical diagnoses in both clinical and research settings [56].…”
Section: Challenging Behaviour and Mental Health Problemsmentioning
confidence: 99%
See 1 more Smart Citation